IPTEKS PELAKSANAAN SEWA BARANG MILIK NEGARA PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) MANADO - Sadil, Cecen A.; Mahyudin, Dede F.; Harikase, Wanly; Morasa, Jenny (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The implementation of BMN Rental is the utilization of other parties within a certain period of time and receive cash rewards that can increase non-tax state revenue (PNBP). Based on the results of observations, it can be seen that the object of lease in the implementation of BMN leases in Manado KPKNL has covered all rental objects above, so Manado KPKNL expects reports from other work units and awareness of satker in reporting BMN after that KPKNL Manado takes investigative actions to the field , there are still many satker who complain about the high cost of rent. BMN leasing in Manado KPKNL is considered to be lacking, because there are still a lot of satker who have not fully understood the requirements for submitting the lease documents, so that when the lease application is submitted there are still many incomplete / incomplete requirements documents. Suggestions from penuis for KPKNL Manado are expected to be able to set a reasonable and affordable BMN rental price. Advice from the author is expected for each Satker to pay more attention to the requirements before applying for BMN rent.Keywords : Rental Implementation, state property (BMN).